A dielectric ceramic material based on barium titanate and a preparation method thereof
By doping cobalt and aluminum in barium titanate material and forming an organic frame with 2-methylimidazole, the problems of high dielectric loss and low breakdown electric field resistance of ceramic dielectric materials are solved, and high dielectric constant and low loss are achieved The preparation of ceramic materials improves the performance of electronic equipment.
Patent Information
- Application Number
- CN202410727590.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-06-06
AI Technical Summary
Ceramic dielectric materials have large dielectric losses and low breakdown electric field resistance, which cannot meet the high dielectric constant and low loss requirements of electronic equipment.
By doping cobalt and aluminum in barium titanate material and polymerizing in situ with 2-methylimidazole to form an organic frame to improve the dielectric constant and breakdown strength, the modified barium titanate powder and polyvinyl alcohol are used. Combined preparation method, ball milling and sintering to make ceramic material.
It significantly improves the dielectric constant and breakdown strength of the material, reduces dielectric loss, and enhances the signal stability and breakdown resistance of the material.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of dielectric ceramic materials, and specifically refers to a dielectric ceramic material based on barium titanate and a preparation method thereof. Background Art
[0002] Dielectric materials, also known as dielectric materials, are electrical insulating materials. The dielectric constant refers to the ratio between its capacitance and vacuum capacitance in the dielectric material, which is related to the capacitance value and polarization degree of the material. Dielectric loss refers to the electrical energy lost in the form of heat consumed by the capacitor during use. The breakdown electric field refers to the electric field corresponding to the dielectric material being finally broken down under the action of the electric field as the electric field strength increases. With the rapid development of the electrical and electronic industries, people's demand for the continuous miniaturization of electronic equipment and signal stability is increasing. Materials with high dielectric constants and low dielectric losses can effectively increase the unit volume capacitance of electronic components, reduce the size of equipment and enhance signal stability, and have great application value. The dielectric materials currently used are mainly ceramic dielectric materials and polymer dielectric materials. Ceramic dielectric materials usually have a high dielectric constant, but the dielectric loss is also large and the breakdown strength is low.
[0003] The existing technology currently has the following main problems: the dielectric loss of ceramic dielectric materials is also large, and the anti-breakdown electric field is low. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a dielectric ceramic material based on barium titanate and a preparation method thereof. In order to solve the problem that the dielectric loss of ceramic dielectric materials is also large and the breakdown resistance electric field is low, the present invention proposes to prepare modified barium titanate powder, dope it with cobalt and aluminum, and in-situ polymerize 2-methylimidazole to form an organic framework, thereby achieving an increase in the dielectric constant of the barium titanate material and improving the breakdown strength.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: The present invention proposes a barium titanate-based dielectric ceramic material, which is prepared from the following components in parts by weight: 100-120 parts of modified barium titanate powder and 0.8-1.2 parts of polyvinyl alcohol.
[0006] Preferably, the modified barium titanate powder is prepared from the following components in parts by weight: 60-66 parts of tetrabutyl titanate, 72-79 parts of barium chloride, 0.6-0.9 parts of cobalt chloride, 0.3-0.5 parts of aluminum nitrate, and 2.4-3.2 parts of 2-methylimidazole.
[0007] Preferably, the method for preparing the modified barium titanate powder specifically comprises the following steps:
[0008] S1. Add tetrabutyl titanate to anhydrous ethanol, add 2.5-3wt% nitric acid solution in an amount 4 times the volume of anhydrous ethanol, stir in a water bath, and obtain a titanium source solution;
[0009] S2, adding barium chloride, cobalt chloride, and aluminum nitrate into deionized water, stirring in a water bath to obtain a mixed barium source solution;
[0010] S3, adding the titanium source solution obtained in S1 to the mixed barium source solution obtained in S2 to obtain a mixed solution, then adding sodium hydroxide and stirring evenly to obtain a cobalt-aluminum-doped barium titanate solution;
[0011] S4. Add 2-methylimidazole to the methanol solution and stir evenly, add it to the cobalt-aluminum-doped barium titanate solution obtained in S3, ultrasonicate at 60-80w for 10-15min, stir in an oil bath, collect the precipitate, wash and dry to obtain modified barium titanate powder.
[0012] Preferably, in S1, the amount of tetrabutyl titanate added to anhydrous ethanol is 0.2-0.3 g / mL;
[0013] Preferably, in S1, the water bath stirring temperature is 60-65°C, the speed is 80-100 rpm, and the time is 30-50 min.
[0014] Preferably, in S2, the amount of barium chloride added to deionized water is 0.3-0.4 g / mL;
[0015] Preferably, in S2, the water bath stirring temperature is 50-60°C, the speed is 60-80 rpm, and the time is 15-25 min.
[0016] Preferably, in S3, the amount of sodium hydroxide added to the mixed solution is 35-45 mg / mL;
[0017] Preferably, in S4, the amount of 2-methylimidazole added to the methanol solution is 0.1-0.2 g / mL;
[0018] Preferably, in S4, the oil bath stirring temperature is 160-180°C, the speed is 100-120 rpm, and the time is 10-15 h.
[0019] The present invention also provides a method for preparing a barium titanate dielectric ceramic material, which specifically comprises the following steps:
[0020] (1) Adding polyvinyl alcohol to the modified barium titanate powder, ball milling with zirconium oxide, with a material-ball ratio of 1:6-8, a rotation speed of 300-400 rpm, and a time of 1-2 hours, and then pressing with a tablet press to obtain a ceramic green body;
[0021] (2) The ceramic green body obtained in step (1) is subjected to debinding at 600° C. for 50-60 min under nitrogen protection, and then sintered at 1200-1300° C. for 2-3 h under nitrogen protection to obtain a barium titanate-based dielectric ceramic material.
[0022] The beneficial effects achieved by the present invention are as follows: tetrabutyl titanate is used as a titanium source, barium chloride is used as a barium source, cobalt chloride and aluminum nitrate are added for cobalt-aluminum doping, and Ba in barium titanate is partially replaced. 2+ or Ti 4+ , changing the crystal structure of barium titanate ceramics, increasing the dielectric constant and reducing dielectric loss; using 2-methylimidazole to in-situ polymerize an organic framework on barium titanate, forming a carbon skeleton after sintering, which can form a large number of electric dipoles on the surface, thereby increasing the dielectric constant of the material, improving the dielectric constant of the material, and enhancing the breakdown strength of the material; using polyvinyl alcohol to bond the powder for ball milling, pressing and sintering, dielectric ceramics of different sizes that meet different needs can be produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The results of dielectric constant test of Examples 1-3 and Comparative Examples 1-3 are shown in FIG.
[0024] Figure 2 The results of dielectric loss test of the dielectric properties of Examples 1-3 and Comparative Examples 1-3 are shown;
[0025] Figure 3 It is a result diagram of the breakdown strength test of Examples 1-3 and Comparative Examples 1-3.
[0026] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0029] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0030] Example 1
[0031] A dielectric ceramic material based on barium titanate is prepared from the following components in parts by weight: 120 parts of modified barium titanate powder and 1.2 parts of polyvinyl alcohol.
[0032] The modified barium titanate powder is prepared from the following components in parts by weight: 66 parts of tetrabutyl titanate, 79 parts of barium chloride, 0.9 parts of cobalt chloride, 0.5 parts of aluminum nitrate, and 3.2 parts of 2-methylimidazole.
[0033] The preparation method of modified barium titanate powder specifically comprises the following steps:
[0034] S1. Add tetrabutyl titanate in anhydrous ethanol at an addition amount of 0.3 g / mL, add 3 wt % nitric acid solution of 4 times the volume of anhydrous ethanol, stir at 100 rpm in a 65° C. water bath for 50 min to obtain a titanium source solution;
[0035] S2, adding barium chloride in an amount of 0.4 g / mL to deionized water, and then adding cobalt chloride and aluminum nitrate in sequence, stirring at 80 rpm in a 60° C. water bath for 25 min to obtain a mixed barium source solution;
[0036] S3, adding the titanium source solution obtained in S1 to the mixed barium source solution obtained in S2 to obtain a mixed solution, then adding sodium hydroxide in an amount of 45 mg / mL, stirring evenly, to obtain a cobalt-aluminum-doped barium titanate solution;
[0037] S4. Add 0.2 g / mL of 2-methylimidazole to the methanol solution and stir evenly. Add the mixture to the cobalt-aluminum-doped barium titanate solution obtained in S3. Ultrasonicate at 80 W for 15 min. Stir in an oil bath at 180 ° C and 120 rpm for 15 h. Collect the precipitate, wash it, and dry it to obtain modified barium titanate powder.
[0038] The present invention also provides a method for preparing a barium titanate dielectric ceramic material, which specifically comprises the following steps:
[0039] (1) Adding polyvinyl alcohol to the modified barium titanate powder, ball milling with zirconium oxide, with a material-ball ratio of 1:8, a rotation speed of 400 rpm, and a time of 2 h, and then pressing with a tablet press to obtain a ceramic green body;
[0040] (2) The ceramic green body obtained in step (1) is subjected to debinding at 600° C. for 60 min under nitrogen protection, and then sintered at 1300° C. for 3 h under nitrogen protection to obtain a barium titanate-based dielectric ceramic material.
[0041] Example 2
[0042] A dielectric ceramic material based on barium titanate is prepared from the following components in parts by weight: 100 parts of modified barium titanate powder and 0.8 parts of polyvinyl alcohol.
[0043] The modified barium titanate powder is prepared from the following components in parts by weight: 60 parts of tetrabutyl titanate, 72 parts of barium chloride, 0.6 parts of cobalt chloride, 0.3 parts of aluminum nitrate, and 2.4 parts of 2-methylimidazole.
[0044] The preparation method of modified barium titanate powder specifically comprises the following steps:
[0045] S1. Add tetrabutyl titanate in anhydrous ethanol at an addition amount of 0.2 g / mL, add 2.5 wt% nitric acid solution with a volume of 4 times that of anhydrous ethanol, stir in a water bath at 60° C. and 80 rpm for 30 min to obtain a titanium source solution;
[0046] S2, adding barium chloride in an amount of 0.3 g / mL to deionized water, and then adding cobalt chloride and aluminum nitrate in sequence, stirring at 60 rpm in a 50° C. water bath for 15 min to obtain a mixed barium source solution;
[0047] S3, adding the titanium source solution obtained in S1 to the mixed barium source solution obtained in S2 to obtain a mixed solution, then adding sodium hydroxide in an amount of 35 mg / mL, stirring evenly, to obtain a cobalt-aluminum-doped barium titanate solution;
[0048] S4. Add 0.1 g / mL of 2-methylimidazole to the methanol solution and stir evenly. Add the mixture to the cobalt-aluminum-doped barium titanate solution obtained in S3. Ultrasonicate at 60 W for 10 min. Stir in an oil bath at 160 ° C and 100 rpm for 10 h. Collect the precipitate, wash it, and dry it to obtain modified barium titanate powder.
[0049] The present invention also provides a method for preparing a barium titanate dielectric ceramic material, which specifically comprises the following steps:
[0050] (1) Adding polyvinyl alcohol to the modified barium titanate powder, ball milling with zirconium oxide, with a material-ball ratio of 1:6, a rotation speed of 300 rpm, and a time of 1 h, and then pressing with a tablet press to obtain a ceramic green body;
[0051] (2) The ceramic green body obtained in step (1) is subjected to debinding at 600° C. for 50 min under nitrogen protection, and then sintered at 1200° C. for 2 h under nitrogen protection to obtain a barium titanate-based dielectric ceramic material.
[0052] Example 3
[0053] A barium titanate-based dielectric ceramic material is prepared from the following components in parts by weight: 110 parts of modified barium titanate powder and 1 part of polyvinyl alcohol.
[0054] The modified barium titanate powder is prepared from the following components in parts by weight: 62 parts of tetrabutyl titanate, 75 parts of barium chloride, 0.8 parts of cobalt chloride, 0.4 parts of aluminum nitrate, and 3 parts of 2-methylimidazole.
[0055] The preparation method of modified barium titanate powder specifically comprises the following steps:
[0056] S1. Add tetrabutyl titanate in anhydrous ethanol at an addition amount of 0.25 g / mL, add 2.8 wt % nitric acid solution with a volume of 4 times that of anhydrous ethanol, stir in a water bath at 62° C. and 90 rpm for 40 min to obtain a titanium source solution;
[0057] S2, adding barium chloride in an amount of 0.35 g / mL to deionized water, and then adding cobalt chloride and aluminum nitrate in sequence, stirring at 70 rpm in a 55° C. water bath for 20 min to obtain a mixed barium source solution;
[0058] S3, adding the titanium source solution obtained in S1 to the mixed barium source solution obtained in S2 to obtain a mixed solution, then adding sodium hydroxide in an amount of 40 mg / mL, stirring evenly, to obtain a cobalt-aluminum-doped barium titanate solution;
[0059] S4. Add 0.15 g / mL of 2-methylimidazole to the methanol solution and stir evenly. Add the mixture to the cobalt-aluminum-doped barium titanate solution obtained in S3. Ultrasonicate at 70 W for 12 min. Stir in an oil bath at 170 ° C and 110 rpm for 12 h. Collect the precipitate, wash it, and dry it to obtain modified barium titanate powder.
[0060] The present invention also provides a method for preparing a barium titanate dielectric ceramic material, which specifically comprises the following steps:
[0061] (1) Adding polyvinyl alcohol to the modified barium titanate powder, ball milling with zirconium oxide, with a material-to-ball ratio of 1:7, a rotation speed of 350 rpm, and a time of 1.5 h, and then pressing with a tablet press to obtain a ceramic green body;
[0062] (2) The ceramic green body obtained in step (1) was debinded at 600° C. for 55 min under nitrogen protection, and then sintered at 1250° C. for 2.5 h under nitrogen protection to obtain a barium titanate-based dielectric ceramic material.
[0063] Comparative Example 1
[0064] This comparative example provides a dielectric ceramic material based on barium titanate, which differs from Example 1 only in that the component does not contain 2-methylimidazole, and the other components and component contents are the same as those in Example 1.
[0065] Comparative Example 2
[0066] This comparative example provides a dielectric ceramic material based on barium titanate, which differs from Example 1 only in that cobalt chloride is replaced by aluminum nitrate in an equimolar amount, and the remaining components and component contents are the same as those in Example 1.
[0067] Comparative Example 3
[0068] This comparative example provides a dielectric ceramic material based on barium titanate, which differs from Example 1 only in that aluminum nitrate is replaced by an equimolar amount of cobalt chloride in the components, and the other components and component contents are the same as those in Example 1.
[0069] Experimental example
[0070] 1. Dielectric properties test
[0071] The dielectric constant and dielectric loss of the barium titanate dielectric ceramic materials obtained in Examples 1-3 and Comparative Examples 1-3 were tested with a widescreen dielectric analyzer. Gold was sprayed on the upper and lower surfaces of the materials as electrodes. The test range was 10 2 -10 6 Hz.
[0072] Figure 1 The dielectric constant results of the dielectric properties test of Example 1-3 and Comparative Example 1-3 are shown in the figure. As shown in the figure, the dielectric constants of Example 1-3 and Comparative Example 1-3 are 1835, 1861, 1846, 733, 936, and 863, respectively; the dielectric constant of Example 1-3 is significantly higher than that of Comparative Example 1-3, indicating that the preparation of the organic framework and co-doping with cobalt and aluminum improve the dielectric constant of the material.
[0073] Figure 2 The dielectric loss results of the dielectric properties test of Examples 1-3 and Comparative Examples 1-3 are shown in the figure. As shown in the figure, the dielectric losses of Examples 1-3 and Comparative Examples 1-3 are 2.1%, 2.3%, 2.2%, 3.5%, 3.1%, and 3.3%, respectively. The dielectric loss of Examples 1-3 is significantly lower than that of Comparative Examples 1-3, indicating that the preparation of the organic framework and the co-doping of cobalt and aluminum reduce the dielectric loss of the material. The Ba of the barium titanate lattice replaced by cobalt and aluminum doping is 2+ and Ti 4+ , changing the crystal structure of barium titanate ceramics, thereby improving its dielectric properties.
[0074] 2. Breakdown strength test
[0075] The breakdown strength (Eb) of the barium titanate dielectric ceramic materials obtained in Examples 1-3 and Comparative Example 1 was tested with a withstand voltage tester. The voltage increase rate was 200 V / s, and the voltage increase range was 0.5-9.999 kV.
[0076] Figure 3It is a result graph of the breakdown strength test of Example 1-3 and Comparative Example 1-3. As shown in the figure, the breakdown strengths of Example 1-3 and Comparative Example 1-3 are 386.3MV / m, 385.4MV / m, 383.6MV / m, 223.6MV / m, 230.3MV / m, and 362.6MV / m, respectively; the breakdown strength of Example 1-3 is significantly higher than that of Comparative Example 1-2, and the breakdown strength of Comparative Example 3 is significantly higher than that of Comparative Example 1-2, indicating that the use of 2-methylimidazole to prepare the organic framework improves the material's anti-puncture performance.
[0077] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0078] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A dielectric ceramic material based on barium titanate, characterized in that: The barium titanate-based dielectric ceramic material is prepared from the following components in parts by weight: 100-120 parts of modified barium titanate powder and 0.8-1.2 parts of polyvinyl alcohol; the modified barium titanate powder is prepared from the following components in parts by weight: 60-66 parts of tetrabutyl titanate, 72-79 parts of barium chloride, 0.6-0.9 parts of cobalt chloride, 0.3-0.5 parts of aluminum nitrate, and 2.4-3.2 parts of 2-methylimidazole; 2-methylimidazole in-situ polymerizes an organic framework on the barium titanate, and forms a carbon skeleton after sintering.
2. A method for preparing a barium titanate-based dielectric ceramic material according to claim 1, characterized in that: The specific steps include: (1) Adding polyvinyl alcohol to the modified barium titanate powder, ball milling with zirconium oxide, with a material-ball ratio of 1:6-8, a rotation speed of 300-400 rpm, and a time of 1-2 hours, and then pressing with a tablet press to obtain a ceramic green body; (2) The ceramic green body obtained in step (1) is subjected to debinding at 600° C. for 50-60 min under nitrogen protection, and then sintered at 1200-1300° C. for 2-3 h under nitrogen protection to obtain a barium titanate-based dielectric ceramic material.
3. The method for preparing a barium titanate dielectric ceramic material according to claim 2, characterized in that: The preparation method of the modified barium titanate powder specifically comprises the following steps: S1. Add tetrabutyl titanate to anhydrous ethanol, add 2.5-3wt% nitric acid solution in an amount 4 times the volume of anhydrous ethanol, stir in a water bath, and obtain a titanium source solution; S2, adding barium chloride, cobalt chloride, and aluminum nitrate into deionized water, stirring in a water bath to obtain a mixed barium source solution; S3, adding the titanium source solution obtained in S1 to the mixed barium source solution obtained in S2 to obtain a mixed solution, then adding sodium hydroxide and stirring evenly to obtain a cobalt-aluminum-doped barium titanate solution; S4. Add 2-methylimidazole to the methanol solution and stir evenly, add it to the cobalt-aluminum-doped barium titanate solution obtained in S3, ultrasonicate at 60-80w for 10-15min, stir in an oil bath, collect the precipitate, wash and dry to obtain modified barium titanate powder.
4. The method for preparing a barium titanate-based dielectric ceramic material according to claim 3, characterized in that: In S1, the amount of tetrabutyl titanate added to anhydrous ethanol is 0.2-0.3 g / mL; the water bath stirring temperature is 60-65° C., the speed is 80-100 rpm, and the time is 30-50 min.
5. The method for preparing a barium titanate-based dielectric ceramic material according to claim 4, characterized in that: In S2, the amount of barium chloride added to deionized water is 0.3-0.4 g / mL; the water bath stirring temperature is 50-60° C., the speed is 60-80 rpm, and the time is 15-25 min.
6. The method for preparing a barium titanate-based dielectric ceramic material according to claim 5, characterized in that: In S3, the amount of sodium hydroxide added to the mixed solution is 35-45 mg / mL.
7. The method for preparing a barium titanate-based dielectric ceramic material according to claim 6, characterized in that: In S4, the amount of 2-methylimidazole added to the methanol solution is 0.1-0.2 g / mL; the oil bath stirring temperature is 160-180° C., the speed is 100-120 rpm, and the time is 10-15 h.
Citation Information
Patent Citations
Amorphous diamond materials and associated methods for the use and manufacture thereof
CN101147426A
Barium titanate based lead-free piezoceramic material added with cobalt and aluminium and preparation method thereof
CN102249671A
Preparation method and application of lead-free piezoelectric ceramic material
CN108275983A
High-dielectric double-sided etched buried capacitor material, preparation method and application thereof
CN111565510A
Preparation method of three-dimensional porous barium titanate composite dielectric material
CN113956618A
